Penerapan Model Pembelajaran Talking Stick Untuk Meningkatkan Kemampuan Mengenal Lambang Bilangan 1-10 Pada Anak Kelompok B Di Paud Kristen Rehobot Manado - Mieke F. Tiwow (Peneliti.net, 2021)
The teacher's lack of knowledge of the learning model used resulted in the learning process at Christian Rehobot Manado PAUD not attracting children's attention. This can be seen from the number of children there are 15 children, and those who already know the symbols for numbers 1-10 there are 5 children while the other 10 children do not know the symbols for numbers 1-10 well. For this reason, the purpose of this research is to describe the increase in the ability to recognize the symbols of numbers 1-10 through the talking stick learning model for children in Christian PAUD Rehobot Manado. The research method used was classroom action research referring to Kemmis & Taggart (in Taniredja, et al 2011: 24) with 4 stages consisting of planning, implementation/action, observation and reflection with two cycles. Data collection techniques were carried out based on observation and interview guidelines. The results achieved in cycle I indicated that the indicators were maximal according to the indicators that there were 5 children while the other 10 children did not know the symbols for numbers 1-10 well. While the results of the second cycle increased, the results of achieving indicators were 12 children who received 4 stars and were declared successful. For this reason, it can be concluded that with the talking stick learning model, the child's ability to recognize the number symbols 1-10 increases.